Aging of the population may not lead to an increase in the numbers of acute coronary events: a community surveillance study and modelled forecast of the future. Issue 13 (18th April 2013) - Salomaa, Veikko; Havulinna, Aki S; Koukkunen, Heli; Kärjä-Koskenkari, Päivi; Pietilä, Arto; Mustonen, Juha; Ketonen, Matti; Lehtonen, Aapo; Immonen-Räihä, Pirjo; Lehto, Seppo; Airaksinen, Juhani; Kesäniemi, Y Antero
Abstract : Objective: To examine the incidence, mortality and case fatality of acute coronary syndrome (ACS) in Finland during 1993–2007 and to create forecasts of the absolute numbers of ACS cases in the future, taking into account the aging of the population. Design: Community surveillance study and modelled forecasts of the future. Setting and methods: Two sets of population-based coronary event register data from Finland (FINAMI and the National Cardiovascular Disease Register (CVDR)). Bayesian age–period–cohort (APC) modelling. Participants: 24 905 observed ACS events in the FINAMI register and 364 137 in CVDR. Main outcome measures: Observed trends of ACS events during 1993–2007, forecasted numbers of ACS cases, and the prevalence of ACS survivors until the year 2050. Results: In the FINAMI register, the average annual declines in age-standardised incidence of ACS were 1.6% (p<0.001) in men and 1.8% (p<0.001) in women. For 28-day case fatality of incident ACS, the average annual declines were 4.1% (p<0.001) in men and 6.7% (p<0.001) in women. Findings in the country-wide CVDR data were consistent with the FINAMI register. The APC model, based on the CVDR data, suggested that both the absolute numbers of ACS events and the prevalence of ACS survivors reached their peak in Finland around 1990, have declined since then, and very likely will continue to decline until 2050. Conclusions: The ACS event rates and absolute numbers of cases have declined steeply in Finland. The declining trends are likely to continue in the future despite the aging of the population.